EVALUASI KEBIJAKAN AKSI PERCEPATAN KONVERGENSI PENURUNAN STUNTING TERINTEGRASI DI KABUPATEN KEPULAUAN SERIBU PROVINSI DKI JAKARTA TAHUN 2021 - novasetianie; Handayani; Rustika (Avicenna: Jurnal Ilmiah, 2023)
Background: Stunting is a continual malnutrition resulting from a loss of nutrient consumption for an extended time ensuing in a short body posture compared to the age standard. Convergence of acceleration of stunting prevention is achieved effectively and efficiently, it is necessary to carry out 8 (eight) Convergen Actions. This Evaluate the performance the Stunting Reducing policy in Kepulauan Seribu, Provinsi DKI Jakarta in 2021. Method use a qualitative a finding out by collecting various information through in-depth interviews and document review. Result, it can be conclude involved in the Action Convergence Prevent Stunting program refer to Intruksi Bupati No. 2 of 2021 where all OPD are involved but do not involve non Governmental elements. Sources of policy in implementing the program considered to still need strengthening in terms regulations and the role of related sectors in supporting the success of the Stunting program, Policy brief, by adding SOP the sub-district and level village. Data and Information uses the e-PPGBM application, whose input for toddlers has reached the total corvarege. Conclusion: Sources of policy Convergence action to accelerate stunting reduction doesn’t require technical guidelines, SOP related the stunting prevention action convergence program facilitate the work structure in Kepulauan Seribu. The plan is proposed to be included in RKPD specifically for stunting in each OPD. Organizing involves the role of non-govermen organisasi academics, professional organizations and CSR. There is a need for MOU with non-government to help accelerate the reduction of stunting in the Kepulauan Seribu. Keywords: evaluation, stunting, and Convergence of Stunting Reduction